Ketidaksetaraan Gender dan Stigma Sosial terhadap Perempuan Pasca Perceraian: Tinjauan dari Perspektif Komunikasi Dakwah - Anggita hikmatul hinayah (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2026)
This study examines gender inequality and social stigma experienced by divorced women within Indonesia's patriarchal society. Gender inequality manifests as social, economic, and legal discrimination, while social stigma compounds the marginalization divorced women already face. Using a qualitative library research design, this study analyzes primary and secondary literature through descriptive-analytical techniques grounded in gender theory and social stigma theory, read alongside the perspective of Islamic da'wah communication. The findings show that divorced women confront negative stereotyping, economic discrimination, social marginalization, and gender-based violence, with patriarchal cultural norms reinforcing these patterns and obstructing their efforts to rebuild independent lives. The study further finds that gender inequality and social stigma are mutually reinforcing rather than separate phenomena, so that reducing one without addressing the other yields limited protection for divorced women. The study also finds that da'wah rhetoric and da'wah media, when guided by persuasive communication principles such as qaulan ma'rufa and qaulan sadidan, hold potential to counter rather than reinforce this stigma. These findings underscore the need for gender-awareness education, legal policy reform, stronger social support systems, and da'wah communication that is more responsive to divorced women. Future research should examine women's resilience strategies, the effects of stigma on children, and the role of da'wah media in either reinforcing or countering stigma, toward building a more inclusive and equitable society.